Fifteen minute consultation: A structured approach to the management of children and adolescents with medically unstable anorexia nervosa. Issue 4 (13th February 2017) - Allison, Elizabeth; Dawson, Nicola; Phillips, Jane; Lynch, Catherine; Coleman, Jacinta
Abstract : Assessing and managing children who are underweight is an integral part of paediatric practice. Young people with anorexia nervosa (AN) are mainly cared for in the community by specialist eating disorder services. However, increasing numbers require admission to paediatric wards with medical instability due to the complications of starvation. Despite recommendations published in the junior MARSIPAN report in 2012, many paediatricians still feel poorly equipped to care for these high-risk patients. This article aims to provide a safe and structured approach to the assessment and management of children and adolescents with medically unstable AN.